Strategisk/taktisk vägplan - Wahn, Johan (2006)
The purpose of this thesis was to create a strategic/tactical road access plan. This was done by designing an analytical method which gives the road manager a template to create long-term road access plans. The analytical method will help to identify and appraise roads to be upgraded and give information when it is time for building new roads.